BERBAGAI PENDEKATAN DALAM MEMAHAMI HADIS - A. Shamad Usman (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2016)
In epistemology. Hadith or Sunnah by Muslims is seen as a source of Islamic teaching second after Koran. For he is the bayan (explanation) of the verses of the Qur'an are still mujmal (global), the 'am (general) and mutlaq (without limitation). Even independently traditions can also serve as a settler (muqarrir) a law that has not been defined by the Qur'an. Therefore, the existence of tradition not only has colored the public in a variety of life, especially in the world of academia, but also has been discussed in the study and research of interest and endless, including methodological approaches and understanding of tradition and its applications.